Bibliometric and multicriteria analysis for selection of amendments potentiators of compost from municipal biowaste - Victor A. L. Sandoval; Johan S. T. Corredor; Sahra N. R. Rincón; Kimberly P. Montañez-Medina (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Municipal biowaste has a high potential for agricultural use. However, it requires an additional amendment to increase the nutritional content used during the composting process. The purpose of this study was to investigate the selection of compost-enhancing amendments from municipal biowaste using bibliometric and multicriteria analysis. The municipality of Yopal (Casanare, Colombia) was chosen as a case study. Using a search equation in the Scopus and Web of Science databases over five years (2018-2022), 53 publications were discovered, from which 25 were chosen for a full review to identify alternatives for amendment. Ashes, rice husks, sawdust, sugarcane bagasse, tree pruning waste, and alfalfa hay were assessed as amendment substitutes. Criteria such as financial cost, accessibility to acquire the amendment, nitrogen, phosphorus, and carbon contribution were used in the analysis of hierarchical processes. Tree pruning waste was the best option based on the criteria chosen because it is easily accessible and contributes with carbon and nitrogen (C/N: 13) to composting. Factors such as cost and affordability influence the physical and chemical characteristics that an amendment brings to the composting of municipal biowaste.